GENETIC PARAMETER ESTIMATES FOR GROWTH TRAITS IN AN Eucalyptus Urophylla S.T. Blake PROGENY TEST IN TIMOR ISLAND - Sumardi, Sumardi; Kurniawan, Hery; Prastyono, Prastyono (Indonesian Journal of Forestry Research, 2016)
Genetic parameters were estimated for growth traits of Ampupu (Eucalyptus urophylla S.T. Blake) progeny test grown in Southern Central Timor - East Nusa Tenggara Province, Timor Island. When the trial was one year old data were collected from 45 half-sib open pollinated families and assessed. There were genetic variations in height and diameter among families of E. urophylla. Growth traits had moderate heritability, both individually and in family, i.e. 0.28 and 0.55 for height and 0.41 and 0.66 for diameter, respectively. Genetic correlation between height and diameter was strong (0.96). However, the estimation of genetic parameter should be interpreted carefully since the trial was very young. Re-assessment of the trial should be carried out periodically to provide better understanding of the species regarding the dynamic of the genetic interaction between the species and its environment, effective age of selection and prediction of genetic gain.